Relationship between diabetic retinopathy and cerebral perfusion in type 2 diabetes mellitus (Ukrainian Journal of Ophthalmology, 2026)
Background: Compared to patients without diabetic retinopathy (DR), those with DR demonstrate better cognitive performance. It is therefore reasonable to hypothesize that retinal microcirculatory changes might be a marker of impaired cerebral microcirculation.Purpose: To examine the association between the presence of diabetic retinopathy and cerebral perfusion in patients with type 2 diabetes mellitus (T2DM).Materials and Methods: Ninety-five T2DM patients aged 50-70 years were enrolled. They were divided into two groups, those with DR (DR group) and without DR (non-DR group). Regional cerebral blood flows (rCBF) were measured with 99mTc-HMPAO single-photon emission computed tomography (SPECT).Results: Linear regression analysis revealed negative relationships between DR and cerebral perfusion impairments in right frontal lobe (B (95% CI) = 0.58 (-0.98/-0.18); P = 0.01), left frontal (B (95% CI) = -0.55 (-0.99/-0.12); P = 0.02) lobe, right parietal lobe (B (95% CI) = -0.68 (-1.19/-0.16); P = 0.01), left parietal lobe (B (95% CI) = -0.79 (-1.31/-0.27); P = 0.00); right occipital lobe (B (95% CI) = -0.61(-1.17/-0.06); P = 0.03), left occipital lobe (B (95% CI) = -0.81 (-1.35/-0.26); P = 0.00); right cerebral cortex (B (95% CI) = -0,58 (-0.98/-0.18); P = 0.01) and left cerebral cortex (B (95% CI) = -0.54 (-91/-0.17); P = 0.01).Conclusions: The findings might indicate that, in diabetic patients, damage to retinal microvessels develops somewhat in parallel with that to the brain.
Keywords: diabetic retinopathy; type 2 diabetes mellitus; cerebral blood flow